Student Literacy Skills Through The Implementation of Assisted by Student Worksheets Based on Local Wisdom "Bau Nyale" - Ika Nurani Dewi; Septiana Dwi Utami; Siti Rabiatul Adawiyah (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This research aims to analyze the effect of guided inquiry learning models assisted by student worksheets (LKPD) based on local wisdom on students' literacy skills. The research used a pre-experimental method with a design employing the one-group pretest-posttest design. The sample in this study consisted of 58 students from the 10th-grade science class at SMAN 1 Lembar. Instruments included tests and non-tests, with data analysis techniques such as LKPD validation analysis, N-gain, and hypothesis testing. The findings of this study indicated that the N-gain for class X MIPA 1 was 0.53 (moderate), while the N-gain for class X MIPA 2 was 0.57 (moderate). The t-test result yielded a significance value of 0.000 < 0.05, indicating that using the guided inquiry learning model assisted by LKPD based on local wisdom significantly affects the literacy skills of SMAN 1 Lembar students. Using local wisdom in science learning can make students feel more connected to the learning material because it is relevant to the context of their daily lives. It can increase their involvement in literacy activities in the learning process because more material is taught so that students can understand concepts better.